FAITH FINANCE AND THE FUTURE: THE UNFOLDING STORY OF PARTICIPATION BANKING IN TÜRKİYE - Bayram , Orkun; ADIGÜZEL, SELMİNAZ (Universitas Airlangga, 2025)
Participation banking is a banking transaction that doesn’t generate profit or loss, provides economic financing for commercial transactions, financing for production activities, shares its profit and loss with the customer, and conducts all banking transactions except interest. Islamic Finance is a system where economic activities are carried out in accordance with Sharia law (Islamic law) and businesses and individuals collect capital in accordance with Islamic rules. Riba, gharar, and gambling are prohibited in this financial system. Obtaining income from illegal sales of pornography, lethal weapons, alcohol, and pork, which are not approved by Sharia law, is legal. Ethical, social responsibility work and transactions that will provide social benefit are carried out in accordance with Sharia law. The prohibition of interest in Islamic belief has led to the establishment of interest-free banks. Participation banks, which evaluate the funds they receive from entrepreneurs in investment transactions, share their equity capital, profit and loss with their customers. The purpose of this research is to conduct research on the emergence of the idea of participation banking in Türkiye and participation banks operating in Türkiye. The concept of banking, various banking, the emergence of participation banking and participation banks operating in Türkiye will be discussed in the research.